Pottery Manufacture at a Neolithic Causewayed Enclosure near Hevringholm, East Jutland - Madsen, Bo; Fiedel, Reno (Journal of Danish Archaeology, 1987)
Pottery Manufacture at a Neolithic Causewayed Enclosure near Hevringholm, East Jutland